Fluid-Structure Interaction in a Pipeline Embedded in Concrete During Water Hammer - Chen, Yu; Zhao, Caihu; Guo, Qiang; Zhou, Jianxu; Feng, Yong; Xu, Kunbo (Frontiers in Energy Research, 2022)
Pipe vibration induced by water hammer frequently emerges in water conveyance system, especially in the hydropower plant or pumped storage power station with long diversion pipelines. This vibration in turn affects the hydraulic pulsation so that undesired fluid-structure interaction (FSI) arises. In this research, attention is given to a pipeline embedded in concrete. A six-equation model was derived to describe the fluid-pipe-concrete interaction considering Poisson coupling and junction coupling. With the elastic and homogeneous hypotheses, an iterative approach was proposed to solve this model, and the results were validated by experiment and classical water-hammer theory. Then dynamic FSI responses to water hammer were studied in a reservoir-pipe-valve physical system. Hydraulic pressure, pipe wall stress and axial motion were discussed with respect to different parameters of concrete. Results obtained by the two-equation model, four-equation model and six-equation model show characteristics of pressure wave and stress wave separately with and without FSI.